Influence of beta adrenergic blockade on effects of physical training in patients with ischaemic heart disease. Issue 1 (July 1982) - Vanhees, L; Fagard, R; Amery, A
Abstract : Reduction in heart rate during submaximal exercise is often used to judge the progress of patients with ischaemic heart disease in the course of a physical training programme. Some patients, however, are treated with beta adrenergic blocking drugs and it remains controversial if chronic beta blockade influences the effects of training and if heart rate remains a useful guide in the evaluation of the state of training of these patients. Male postinfarction patients, 15 treated with and 15 without beta blockers, were trained for three months, three times a week. Cardiorespiratory results from uninterrupted incremental exercise tests before and after training were compared. In each subgroup, the heart rate and systolic blood pressure were significantly reduced. For heart rate the decrease after training became more pronounced with increasing work load and the overall reduction was significantly less in the beta blocker group compared with the patients not treated with beta blockers. For systolic blood pressure the training-induced reductions were more pronounced in the patients on beta blockers. The increase of peak oxygen uptake was similar in the patients with and without beta blockers, namely 36% and 34.5%. At submaximal exercise carbon dioxide output, pulmonary minute ventilation, and the respiratory exchange ratio were lower after training, and these effects of training were similar whether or not the patients were on beta blockers. The study shows that the usual effects of training are observed in patients on beta blockers, and that heart rate remains a useful guide to their evaluation throughout a physical training programme.